Effects of perceived control on thermal response and cooling carbon emissions across different operation modes - Dongyu Lu; Haiyan Yan; Guodong Yuan; Hui Zhang; David Chow; Lihua Zhao (Scientific Reports)
Abstract Human psychological adaptation to indoor thermal conditions, particularly through perceived control, is increasingly recognized for its potential to influence building energy consumption. Despite this, its quantifiable impact remains unexplored. Here, we conducted a field survey (n = 922) using air conditioning (AC) access as a variable to examine how perceived control mediates occupants’ thermal adaptation during summer. The perceived control levels of occupants were collected in the form of voting. Before the installation of AC, improved perceived control mitigated thermal sensation in warm environments (> 30.5 ℃). After being granted operational rights to AC, the tolerance of the occupants to the warm environment increased. Using DesignBuilder and EnergyPlus, we modeled and simulated building energy consumption, revealing that increased perceived control could reduce cooling-related carbon emissions by up to 46.6% per day. This study highlights the role of psychological factors in energy sustainability within built environments.